The UN Convention on the Rights of Persons with Disabilities Multi-Level Comparative Study of Legal and Political Implementation in Germany, Austria and Denmark - Grigoryan, Lilit (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The UNCRPD requires the implementation of new structures that promote a paradigm shift in disability rights policy. This book examines how selected EU member states are implementing the provisions, in particular the role of public authorities, monitoring mechanisms and disability organisations. In order to identify and depict the implementation of the UNCRPD and the role of relevant actors, the author applied the concept of multi-level governance and used the method of comparative policy analysis, e.g. the case study approach, as well as data collection techniques. The book will be of particular interest to researchers in the field of disability law and policy, policymakers, and disability rights and human rights organisations.